2015
DOI: 10.3892/ol.2015.3387
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of elasticity imaging and contrast-enhanced ultrasound in the diagnosis of papillary thyroid microcarcinoma

Abstract: Abstract. The present study aimed to evaluate the value of elasticity imaging and contrast-enhanced ultrasonography (CEUS) in the differential diagnosis of papillary thyroid microcarcinoma (TMC). In total, 73 patients exhibiting a total of 80 small thyroid nodules, which were difficult to diagnose using conventional ultrasonography, underwent elasticity imaging and CEUS. The diagnostic findings were subsequently clarified by intraoperative and pathological examination, and the accuracy of the 2 diagnostic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 30 publications
1
30
1
Order By: Relevance
“…Jebreel et al (27) reported that Vascular endothelial growth factor (VEGF) immunostaining was stronger in thyroid cancer, thyroiditis and Graves' disease than in adjacent normal thyroid tissues. Therefore, the differences in the microvessel density of benign and malignant nodules may not be evident when lesions < 1 cm in diameter (23). In the present study, 13 PTMC (8.7%) exhibited iso-or hyper-enhancement in the lesions and surrounding tissues.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Jebreel et al (27) reported that Vascular endothelial growth factor (VEGF) immunostaining was stronger in thyroid cancer, thyroiditis and Graves' disease than in adjacent normal thyroid tissues. Therefore, the differences in the microvessel density of benign and malignant nodules may not be evident when lesions < 1 cm in diameter (23). In the present study, 13 PTMC (8.7%) exhibited iso-or hyper-enhancement in the lesions and surrounding tissues.…”
Section: Discussionmentioning
confidence: 45%
“…In previous studies, researchers have demonstrated that, under CEUS, ring enhancement showed an accuracy of 88.5% for benign lesions, and heterogeneous enhancement showed an accuracy of 90.4% for malignant lesions (22). Li et al (23) concluded that low, weak, or uneven enhancements are valuable perfusion features for evaluating papillary thyroid carcinoma but that a uniform, high-enhanced perfusion mode was typical of benign nodules. In the present study, we confirmed that the following features such as enhancement intensity and rim-like en-6 Iran J Radiol.…”
Section: Discussionmentioning
confidence: 99%
“…Additional parameters will need to be considered for the development of a thorough predictive model. Previously developed algorithms for diagnosing thyroid nodules have integrated ES analysis (26,27). In a study of 141 nodules, most of the benign nodules scored in the range 2-3, while malignant nodules scored ~5 (26).…”
Section: Discussionmentioning
confidence: 99%
“…meta-regression analysis did not show that nodular size was a source of heterogeneity. Several studies reported that CEUS features were closely related to nodule size [31,39]. Yuan et al [39] implied in thyroid cancers less than 1 cm in diameter, the hypoenhancement was more common than thyroid cancers with diameters greater than 2 cm.…”
Section: Plos Onementioning
confidence: 99%
“…Several studies reported that CEUS features were closely related to nodule size [31,39]. Yuan et al [39] implied in thyroid cancers less than 1 cm in diameter, the hypoenhancement was more common than thyroid cancers with diameters greater than 2 cm. Ma's [31] research showed that heterogeneous enhancement was an independent predictor for predicting papillary thyroid microcarcinoma (PTMC).…”
Section: Plos Onementioning
confidence: 99%